2017
DOI: 10.1016/j.jclinepi.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

“Better” clinical decisions do not necessarily require more time to make

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Other research has used patient scenarios to investigate primary care physicians' simulated antibiotic prescribing for upper respiratory tract infection. The study found that evidence-based (no prescribing) decisions were more likely when difficulty with decision-making was lower and decision time was shorter, indicating that appropriate prescribing decisions can be made quickly using a less effortful cognitive process (McCleary et al, 2017). These results consistently show that rapid clinical actions may involve the use of intuitive processes and can be as accurate as clinical actions involving reflective processes, supporting their appropriateness in clinical settings, which may be contrary to popular belief that careful reflection is always favoured.…”
Section: Presence Of Old Cuesmentioning
confidence: 94%
“…Other research has used patient scenarios to investigate primary care physicians' simulated antibiotic prescribing for upper respiratory tract infection. The study found that evidence-based (no prescribing) decisions were more likely when difficulty with decision-making was lower and decision time was shorter, indicating that appropriate prescribing decisions can be made quickly using a less effortful cognitive process (McCleary et al, 2017). These results consistently show that rapid clinical actions may involve the use of intuitive processes and can be as accurate as clinical actions involving reflective processes, supporting their appropriateness in clinical settings, which may be contrary to popular belief that careful reflection is always favoured.…”
Section: Presence Of Old Cuesmentioning
confidence: 94%
“…There were no differences in overall diagnostic accuracy between groups, but within both groups there was a negative correlation between accuracy and time, with cases diagnosed incorrectly taking significantly longer than cases diagnosed correctly. Further evidence using patient scenarios to investigate primary care physicians' simulated antibiotic prescribing for upper respiratory tract infection found that appropriate (no prescribing) decisions were more likely when difficulty with decision-making was lower and decision time was shorter, indicating that appropriate prescribing decisions can be made quickly using a less effortful cognitive process (McCleary et al, 2017). These results consistently show that rapid clinical actions may involve the use of intuitive processes and can be as accurate as clinical actions involving reflective processes, supporting their appropriateness in clinical settings, which may be contrary to popular belief that careful reflection is always favoured.…”
Section: Reflective Impulsive Model (Rim)mentioning
confidence: 99%
“…77 Inappropriate prescribing is related to clinical signs and symptoms, longer time in practice, 78 higher workload, time pressure, fear of complications, diagnostic uncertainty, and perceived 79 patient expectations 3,4 . Also, physicians may prescribe antibiotics when not clinically 80 indicated to maintain good relationships and avoid conflict 5 .…”
mentioning
confidence: 99%
“…Also, physicians may prescribe antibiotics when not clinically 80 indicated to maintain good relationships and avoid conflict 5 . Few studies have investigated 81 the influence of multiple factors simultaneously 3,4 , and it is not clear how these factors come 82 in to play at the moment of making a prescribing decision. Improving our understanding of 83 this could contribute to the design of more effective practice improvement interventions, 84 which often fail to address the specific factors influencing prescribing 6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation